ANSWER: "c=3+\\sqrt { 3 }"
EXPLANATION: On the segment [4,6] the function"g(x)=\\frac { x-4 }{ x-3 } =1-\\frac { 1 }{ x-3 }" is differentiable, therefore by the mean value theorem , exists a point "(c,g(c))" which the tangent line is parallel to the secant connecting the secant connecting the endpoints of the graph. Secant slope is "\\frac { g(4)-g(6) }{ 4-6 } =\\frac { 0-\\frac { 2 }{ 3 } }{ -2 } =\\frac { 1 }{ 3 }" . Tangent slope is
"g'(c)= \\frac { 1 }{ { \\left( c-3 \\right) }^{ 2 } } \\ =\\frac { 1 }{ 3 }" . Hence, "c=3+\\sqrt { 3 } ,\\quad g(c)=1-\\frac { 1 }{ \\sqrt { 3 } }"
Comments
Leave a comment